T cell activation and IFNγ modulate organ dysfunction in LPS-mediated inflammation. Issue 2 (9th February 2022) - Taylor, Matthew D; Fernandes, Tiago D; Yaipen, Omar; Higgins, Cassidy E; Capone, Christine A; Leisman, Daniel E; Nedeljkovic-Kurepa, Ana; Abraham, Mabel N; Brewer, Mariana R; Deutschman, Clifford S
Abstract: LPS challenge is used to model inflammation-induced organ dysfunction. The effects of T cell activation on LPS-mediated organ dysfunction and immune responses are unknown. We studied these interactions through in vivo administration of anti-CD3ε (CD3) T cell activating antibody and LPS. Mortality in response to high-dose LPS (LPSHi; 600 μg) was 60%; similar mortality was observed with a 10-fold reduction in LPS dose (LPSLo; 60 μg) when administered with CD3 (CD3LPSLo). LPSHi and CD3LPSLo cohorts suffered severe organ dysfunction. CD3LPSLo led to increased IFNγ and IL12p70 produced by T cells and dendritic cells (cDCs) respectively. CD3LPSLo caused cDC expression of CD40 and MHCII and prevented PD1 expression in response to CD3. These interactions led to the generation of CD4 and CD8 cytolytic T cells. CD3LPSLo responded to IFNγ or IL12p40 blockade, in contrast to LPSHi. The combination of TCR activation and LPS (CD3LPSLo) dysregulated T cell activation and increased LPS-associated organ dysfunction and mortality through T cell and cDC interactions. Graphical Abstract: T cell activation reduces the lethal dose of lipopolysaccharide 10-fold with major alterations in the immunological responses, while causing similar clinical outcomes.